Perancangan Strategi Pemasaran Jasa Desain Kapal Pada Pt Terafulk Megantara Design Dengan Metode Swot Dan Qspm Sebagai Upaya Peningkatan Daya Saing - Bimata, Weldayana Atyanta; Nadlifatin, Reny (Syntax Literate, 2025)
Marketing strategy is very necessary for a company so that it is attempted to determine the direction by identifying in terms of the market, competitors, and customers. PT Terafulk Megantara Design is a company engaged in the field of ship design services. Contract value revenue has experienced a fluctuating trend, but in 2023 there was a very significant decline compared to the previous year. While the number of contracts also experienced a fluctuating trend and tended to decline, in 2023 the number of contracts experienced a significant increase but was not balanced by the contract value where the contract value in 2023 experienced a significant decline. This shows that a strategy is needed to achieve optimal and balanced revenue targets with the number of contracts worked on. The Quantitative Strategic Planning Matrix (QSPM) method will be used in this study to assist companies in identifying and evaluating various alternative marketing strategies. The analysis process will be carried out through a series of structured methodological stages. It is expected to provide a quantitative approach in choosing the marketing strategy that best suits the company's conditions. Data will be collected through in-depth interviews and participatory observations, and supported by literature related to marketing in the service and shipping industries. The results of this study position PT Terafulk is located in Quadrant I, known as the "Grow & Build" zone. Based on the IFE score of 3.25 and EFE of 3.32, it can be concluded that PT Terafulk has balanced internal strengths and external opportunities. In this situation, the company has a strong foundation to support an aggressive growth strategy. Strategies that can be implemented include new product development, market expansion, and increased innovation to increase competitiveness.